Interferon-Beta Increases Plasma Ceramides of Specific Chain Length in Multiple Sclerosis Patients, Unlike Fingolimod or Natalizumab - Ottenlinger, Florian M.; Mayer, Christoph A.; Ferreirós, Nerea; Schreiber, Yannick; Schwiebs, Anja; Schmidt, Katrin G.; Ackermann, Hanns; Pfeilschifter, Josef M.; Radeke, Heinfried H. (Frontiers in Pharmacology, 2016)
Fingolimod is used for the treatment of multiple sclerosis (MS) and targets receptors for the bioactive sphingolipid sphingosine-1-phosphate. Whether fingolimod or other MS therapies conversely affect plasma concentrations of sphingolipids has, however, not yet been analyzed. Herein, we quantified 15 representative sphingolipid species by mass spectrometry in plasma from relapsing-remitting MS patients currently under fingolimod (n=24), natalizumab (n=16) or IFN-β (n=18) treatment. Healthy controls (n=21) and untreated MS patients (n=11) served as control groups. IFN-ß treatment strongly increased plasma level of C16:0, C18:0, C20:0 and C24:1 ceramides compared to healthy controls, untreated patients, or patients receiving fingolimod or natalizumab medication. Natalizumab treatment increased plasma concentrations of both sphingosine-1-phosphate and sphinganine-1-phosphate, whereas fingolimod treatment did not affect any of these lipids. Correlations of sphingolipids with the Expanded Disability Status Scale and other disease specific parameters revealed no systemic change of sphingolipids in MS, independent of the respective treatment regime. These results indicate type I interferon treatment to cause a strong and specific increase in ceramide level. If confirmed in larger cohorts, these data have implications for the efficacy and adverse effects of IFN-β. Moreover, quantification of ceramides soon after therapy initiation may help to identify therapy-responsive patients.